Sobre o Teorema da Alfândega - Santos, Débora Cristina Lopes dos [UNESP] (2014)
In this dissertation we discuss the Theorem of Customs and its applications, among which we underline the theorem of intermediate value. Therefore, we had to remind some information such as the basic language of topology and connectivity, so we could reach our main objective, the of Customs Theorem. We intend to show the importance of this theorem that unfolds in many applications